Neuropsychiatric and vascular manifestations of disseminated lupus erythematosus. - Correia, J de A (1991)
Disseminated lupus erythematous is an auto-immune disease with systemic manifestations that develops by outbreaks. It's pathogenesis is unknown. The physiopathology jeopardizes auto-immune phenomenon whose most important biological effect is the polyclonal activation of B Lymphocytes. The tissue's lesions are due to several mechanisms, being, perhaps, the deposition of immune complexes of a great value. On account of a young woman with recurrent deep venous thrombosis and neuropsychiatric manifestations the bibliographic data are reviewed, especially those that concern with the etiopathogenesis, treatment and prognosis.